Promoting and Maintaining Changes in Smoking Behavior for Patients Following Discharge from a Smoke-free Mental Health Inpatient Stay: Development of a Complex Intervention Using the Behavior Change Wheel. Issue 4 (17th October 2022) - Shoesmith, Emily; Huddlestone, Lisa; Pervin, Jodi; Shahab, Lion; Coventry, Peter; Coleman, Tim; Lorencatto, Fabiana; Gilbody, Simon; Leahy, Moira; Horspool, Michelle; Paul, Claire; Colley, Lesley; et al.
Abstract: Introduction: Evidence suggests that smokers can successfully quit, remain abstinent or reduce smoking during a smoke-free mental health inpatient stay, provided behavioral/pharmacological support are offered. However, few evidence-based strategies to prevent the return to prehospital smoking behaviors post-discharge exist. Aims and Methods: We report the development of an intervention designed to support smoking-related behavior change following discharge from a smoke-free mental health stay. We followed the Behavior Change Wheel (BCW) intervention development process. The target behavior was supporting patients to change their smoking behaviors following discharge from a smoke-free mental health stay. Using systematic reviews, we identified the barriers and enablers, classified according to the Theoretical Domains Framework (TDF). Potential intervention functions to address key influences were identified by consulting the BCW and Behavior Change Technique (BCT) taxonomy. Another systematic review identified effectiveness of BCTs in this context. Stakeholder consultations were conducted to prioritize and refine intervention content. Results: Barriers and enablers to supporting smoking cessation were identified within the domains of environmental context and resources (lack of staff time); knowledge (ill-informed interactions about smoking); social influences, and intentions (lack of intention to deliver support). Potential strategies to address these influences included goal setting, problem-solving, feedback, social support, and information on health consequences. A strategy for operationalizing these techniques into intervention components was agreed upon: Pre-discharge evaluation sessions, a personalized resource folder, tailored behavioral and text message support post-discharge, and a peer interaction group, delivered by a trained mental health worker. Conclusions: The intervention includes targeted resources to support smoking-related behavior change in patients following discharge from a smoke-free mental health setting. Implications: Using the BCW and TDF supported a theoretically and empirically informed process to define and develop a tailored intervention that acknowledges barriers and enablers to supporting smoking cessation in mental health settings. The result is a novel complex theory- and evidence-based intervention that will be formally tested in a randomized controlled feasibility study.